Ultra-endurance coaxial-fiber stretchable sensing systems fully powered by sunlight - Zhang, Qichong (2020)
Multifunctional integrated devices represent the development direction of future wearable smart electronics. Increased efforts have recently been devoted to developing fiber-shaped integrated devices due to their excellent flexibility and wearability. Fiber-shaped integrated devices combining energy harvest-storage and storage-utilization have been developed. However, the design and development of a single fiber capable of energy harvest, storage, and utilization, although highly desirable, remains greatly challenging. Herein, we successfully assembled a fully solar-powered coaxial-fiber stretchable sensing system by integrating solar cells, a ZnMnO2 battery, and a stretchable strain sensor to simultaneously realize energy harvest, storage, and utilization. Specifically, the harvested solar energy can be effectively converted into electricity by the solar cells and further stored as chemical energy in the stretchable ZnMnO2 battery. More importantly, the solar-charged stretchable ZnMnO2 battery provides a steady and continuous power supply for the stretchable fibrous strain sensor. Thus, this work provides proof-of-concept design for next-generation multifunctional integrated devices.